The interactions of CdTe quantum dots with serum albumin and subsequent cytotoxicity: the influence of homologous ligands. Issue 2 (2nd February 2018) - Yan, Ren; Yu, Bing-Qiong; Yin, Miao-Miao; Zhou, Zhi-Qiang; Xiang, Xun; Han, Xiao-Le; Liu, Yi; Jiang, Feng-Lei
Graphical Abstract: Abstract: With spreading applications of fluorescent quantum dots (QDs) in biomedical fields in recent years, there is increasing concern over their toxicity. Among various factors, surface ligands play critical roles. Previous studies usually employed QDs with different kinds of surface ligands, but general principles were difficult to be obtained since it was hard to compare these surface ligands with varied chemical structures without common features. Herein, the physicochemical properties of two types of CdTe QDs were kept very similar, but different in the surface ligands with mercaptoacetic acid (TGA) and 3-mercaptopropionic acid (MPA), respectively. These two types of homologous ligands only had a difference in one methylene group (–CH2 –). The interactions of the two types of CdTe QDs with bovine serum albumin (BSA), which was one of the main components of cell culture, were studied by fluorescence, UV-vis absorption, and circular dichroism spectroscopy. It was found that the fluorescence quenching of BSA by CdTe QDs followed a static quenching mechanism, and there was no obvious difference in the Stern–Volmer quenching constants and binding constants. The thermodynamic parameters of the two types of QDs were similar. BSA underwent conformational changes upon association with these QDs. By comparing the cytotoxicity of these two types of QDs, TGA-capped QDs were found to be less cytotoxic than MPA-capped QDs. Besides, in the presence of serum proteins, the cytotoxicity of the QDs was reduced. QDs in the absence of serum proteins had a higher internalization efficiency, compared with those in the medium with serum. To the best of our knowledge, this is a rare study focusing on surface ligands with such small variations at the biomolecular and cellular levels. These findings can provide new insights for the design and applications of QDs in complex biological media.